Nanostructured Calcium Phosphates: Preparation and Their Application in Biomedicine - Feng Chen; Yingjie Zhu; Jin Wu; Peng Huang; Daxiang Cui (Nano Biomedicine and Engineering, 2012)
Due to the similar chemical properties to the inorganic component in calcified tissues, synthetic calcium phosphate has been considered as ideal biomaterials with excellent biocompatibility. Nanostructured calcium phosphate materials play an important role in the formation of hard tissues in nature. It is reported that calcium phosphates materials in nano-size can mimic the dimensions of constituent components of calcified tissues. Recently, the synthesis and application of nanostructured calcium phosphate materials have become a very hot field. Lots of methods have been reported to prepare nanostructured calcium phosphate, and various morphologies including nanoparticles, plate-like nanocrystals, nano-needles, whiskers/fibres/wires, mesoporous, nanotubes, nano-blades, and powders with three-dimensional (3-D) structures have been obtained. More studies of nanostructured calcium phosphates are expected in biomedical area, such as tissue engineering scaffolds, drug/gene delivery systems and multifunctional systems. In this article, the synthesis and application of nanostructured calcium phosphates are reviewed and discussed.